PENGARUH JENIS PELARUT TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK MENIRAN (Phyllanthus niruri L.) - Amalia Rachmawati, Rizky; Wisaniyasa, Ni Wayan; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 4 (2020): Jurnal ITEPA, 2020)
This study was conducted to determine the effect of different solvents on the antioxidant activity of gale of the wind extract and to find out the right type of solvent used to extract gale of the wind with the highest antioxidant activity using maceration method. The experimental design used in this study was a completely randomized design (CRD) with a type of solvent as a treatment. The treatment consisting of four levels, namely methanol, ethanol, acetone, isopropanol. All treatments were repeated four times so that they were obtained 16 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect followed by Duncan test. The results showed that the type of solvent treatment had a very significant effect on yield, total phenol, total flavonoids, total tannin, and antioxidant activity (IC50). The results showed that acetone solvent had the best treatment which produced a yield of 22.58%, total phenol content of 188.77 mg GAE/g, total flavonoid content of 247.60 mg QE/g, total tannin content of 297.51mg TAE/g, and antioxidant activity (IC50) of 15.19 ppm.